Yoga, meditation, and mysticism contemplative universals and meditative landmarks - Rose, Kenneth 1951- (London Bloomsbury, 2016)
"Pioneering the exploration of contemplative practice and experience with a comparative perspective that ranges over multiple religious traditions, religious studies, philosophy, neuroscience, and the cognitive science of religion, this book is a landmark contribution to the fields of contemplative practice and religious studies"--Provided by publisher.
A new comparative religion and the search for contemplative universals -- Recovering the mystical in the reign of constructivism -- Biological essentialism and the new sciences of religion -- Charting the common itinerary of the contemplative experience -- The concentrative itinerary of the Buddhist Jhonas -- The concentrative itinerary of Yogic Samodhi -- The concentrative itinerary of Catholic Unio Mystica.
Includes bibliographical references (pages 219-237) and index.
Keywords: Meditation; Contemplation